KONTRIBUSI KEKUATAN OTOT PERUT TERHADAP KEMAMPUAN HEADING PEMAIN SEPAKBOLA CAHAYA MOTOR FC - Amriusman Ndruru; Cundra Bahar; Roki Putra (IICLS (Indonesian Institute for Corporate Learning and Studies), 2023)
Based on the researcher's monitoring of the phenomena that occur in the field, the researcher suspects that the abdominal muscle strength of Cahaya Motor FC Padang football players is still far from expected, this is evident from: the strength of the player in heading the ball is weak, the ball that is headed is not on target and does not arrive at the destination. The purpose of this research is